Exploring Vowel to Vowel Linking Patterns in Spoken English: A Phonetic Perspective: Exploring Vowel to Vowel Linking Patterns in Spoken English: A Phonetic Perspective - Umar Bakri (Pendidikan Al-Gafari, 2026)
The phenomenon of linking in English pronunciation is one of the phonetic aspects that plays an important role in the fluency and naturalness of speech. One common form of linking found in natural conversation is vowel-to-vowel linking, which refers to the connection between a vowel sound at the end of a word and a vowel sound at the beginning of the following word. This study aims to analyze the phonetic characteristics of vowel-to-vowel linking, its patterns of occurrence, and its influence on speaking fluency. The research employs a descriptive qualitative approach by analyzing recorded speech data from English speakers. The data are examined using both segmental and suprasegmental phonetic approaches to identify the types of linking that occur. The results indicate that vowel-to-vowel linking is most frequently realized through the use of the semivowel sounds /j/ and /w/ as bridging elements between vowels. These findings suggest that mastery of linking can enhance speaking fluency and listener comprehension. This study is expected to contribute to the teaching of English pronunciation, particularly in improving learners’ connected speech skills